Anatomy of the coracoid process in Thais: Cadaveric study and clinical implications - Danaithep Limskul; Jirun Apinun; Thanasil Huanmanop; Somsak Kuptniratsaikul (Elsevier, 2022)
Introduction: The aim of this study was to investigate the morphology of the coracoid process and its relationship to body height in Thai cadavers. Materials and methods: Thirty-four shoulders were dissected, and the coracoid processes were measured for their length, width, thickness, and coracohumeral distance. The association between measured values and body height was analyzed. Results: The mean dimension of the coracoid process was 13.1 ± 2.3 mm in width (range 9.6-19.3 mm), 23.7 ± 4.8 mm in length (range 14.4-33.3 mm), and 8.9 ± 1.4 mm in thickness (range 6.7-12.5 mm). The mean coracohumeral distance (CHD) was 9.3 ± 2.1 mm (range 5.6-14.1 mm). Pearson's correlation showed a positive correlation between body height and coracoid width (r = 0.36, p < 0.05) and coracoid thickness (r = 0.50, p < 0.01). Male cadavers showed significantly thicker (p < 0.001) and wider (p < 0.003) coracoids compared to those of females, but not length or CHD. The mean coracoid width for male was 14.6 ± 2.2 mm (range 11.1-19.3 mm) and female was 12.1 ± 1.8 mm (range 11.3-13.1 mm). The mean coracoid thickness for male was 9.8 ± 1.6 mm (range 6.7-12.5 mm) and female was 8.4 ± 1.0 mm (6.7-10.4 mm). Conclusions: The morphology of the coracoid is influenced by sex and body height. The coracoid thickness and width of the cadavers correlate with body height, but not length or CHD. These findings may help predict the size of the coracoid when surgery involves coracoid size determination.